2022
DOI: 10.4196/kjpp.2022.26.5.347
|View full text |Cite
|
Sign up to set email alerts
|

Activating transcription factor 4 aggravates angiotensin II-induced cell dysfunction in human vascular aortic smooth muscle cells via transcriptionally activating fibroblast growth factor 21

Abstract: Abdominal aortic aneurysm (AAA) is a life-threatening disorder worldwide. Fibroblast growth factor 21 (FGF21) was shown to display a high level in the plasma of patients with AAA; however, its detailed functions underlying AAA pathogenesis are unclear. An in vitro AAA model was established in human aortic vascular smooth muscle cells (HASMCs) by angiotensin II (Ang-II) stimulation. Cell counting kit-8, wound healing, and Transwell assays were utilized for measuring cell proliferation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…showed that the changes in the expression of FGF21 under endoplasmic reticulum (ER) stress are caused by the binding of ATF4 to the FGF21 promoter, thus promoting the transcription of FGF21 ( 40 ). Similar results were also observed in ChIP and luciferase reporter assays, which confirmed that AFT4 can bind to the promoter of FGF21 to promote the expression of FGF21 ( 41 ). Moreover, TRIB3 (Tribbles homolog 3), another cellular stress-inducible gene, could inhibit FGF21 expression by binding to ATF4 at the promoter of FGF21 ( 42 ).…”
Section: Transcriptional Regulation Of Fgf21supporting
confidence: 78%
“…showed that the changes in the expression of FGF21 under endoplasmic reticulum (ER) stress are caused by the binding of ATF4 to the FGF21 promoter, thus promoting the transcription of FGF21 ( 40 ). Similar results were also observed in ChIP and luciferase reporter assays, which confirmed that AFT4 can bind to the promoter of FGF21 to promote the expression of FGF21 ( 41 ). Moreover, TRIB3 (Tribbles homolog 3), another cellular stress-inducible gene, could inhibit FGF21 expression by binding to ATF4 at the promoter of FGF21 ( 42 ).…”
Section: Transcriptional Regulation Of Fgf21supporting
confidence: 78%
“…[26] In addition, FGF-21 activation exacerbates aortic smooth muscle cell dysfunction, thereby exacerbating AAA. [27] Xie et al found that FGF21 levels were positively correlated with AAA diameter, hypertension rate and hsCRP by measuring FGF-21 expression levels in AAA and normal human serum. [28] Although relevant studies reported that CCL11 and FGF-21 were upregulated in AAA serum, we still wanted to validate them again, so we performed ELISA validation of 5 proteins in control and abdominal aortic aneurysm groups.…”
Section: 2comparison Of Olink Proteomics In Abdominal Aortic Aneurysm...mentioning
confidence: 99%